show that tan 48°tan23°tan42°tan67°=1
Answers
Answered by
13
L.H.S
◆tan48°tan42° tan23°tan67°
=tan (90 - 42) tan42° tan(90 -67) tan 67°
= cot42° tan42° cot67°tan67°
= (1/tan42°× tan42)° (cot67° ×1/cot67° )
= 1×1 = 1 ,R.H.S
◆hope it helps ◆
◆tan48°tan42° tan23°tan67°
=tan (90 - 42) tan42° tan(90 -67) tan 67°
= cot42° tan42° cot67°tan67°
= (1/tan42°× tan42)° (cot67° ×1/cot67° )
= 1×1 = 1 ,R.H.S
◆hope it helps ◆
lalith482:
How( 90_42)???
Answered by
4
Answer:
Ur ansr mate...
Hope it helps you. .
Step-by-step explanation:
Attachments:
![](https://hi-static.z-dn.net/files/de0/7b0ea4fccbf8c040dcb07e0c18863da5.jpg)
Similar questions